An experimental study of the physical properties of lime mortar and their effect on lime-mortar masonary - Costigan, Adrian (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
The objective of this research is to provide new data in respect to the mechanical behaviour of lime mortar and masonry traditionally used in Ireland, especially the effect of water content and curing time and curing environment. To this end, highly porous bricks with low stiffness and cut and broken limestone, as well as sandstone units were selected. Cement-lime (M6), calcium lime (CL90-S) and natural hydraulic lime (NHL) mortars were manufactured to two flows (165 and 170 mm). The impact of the mortar’s compressive and flexural strengths, and elastic modulus on the compressive and bond strengths of the respective masonry was investigated.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin